Immune-related generalised oedema – A new category of adverse events with immune checkpoint inhibitors. (January 2023) - Velev, Maud; Baroudjian, Barouyr; Pruvost, Roxane; De Martin, Eleonora; Laparra, Ariane; Babai, Samy; Teysseire, Sandra; Danlos, François-Xavier; Albiges, Laurence; Bernigaud, Charlotte; Benderra, Marc-Antoine; Pradère, Pauline; et al.
Abstract: Background: Generalised oedema was occasionally reported associated with immune checkpoint inhibitors (ICPIs). The purpose of this study is to investigate immune-related generalised oedema (ir-GE) drug related to ICPI, through frequency, clinical and pathological characteristics, and patient's outcome. Patients and methods: Objectives of the study were to report on ir-GE associated with ICPI to define frequency, associated signs and symptoms, pathological characteristics, severity, and response to corticosteroids. To be included in the study, adult patients had to have ir-GE related to ICPI with certain or likely link, without any other known causes of generalised oedema. The study design was observational, over the period 2014–2020, from pharmacovigilance databases in France, including the prospective Registre des Effets Indésirables Sévères des Anticorps Monoclonaux Immunomodulateurs en Cancérologie (REISAMIC) registry. Calculation of the frequency of ir-GE was restricted to the prospective REISAMIC registry. Results: Over 6633 screened patients, 20 had ir-GE confirmed drug related to ICPI. Based on the prospective REISAMIC registry, the frequency of ir-GE was 0.19% of ICPI-treated patients (3 cases out of 1598 screened patients). The 20 patients with ir-GE had a median (range) age of 62 (26–81) years, most frequent tumour types were melanoma (n = 9; 45%) and lung cancer (n = 6; 30%). The most frequent localisations of oedema were peripheral (n = 17; 85%), pleural (n = 13; 65%), and peritoneal (n = 10; 50%). Polyserositis was observed in 11 (55%) patients. The median (range) weight gain per patient was 9 (2–30) kg. Associated signs and symptoms met criteria for capillary leak syndrome (n = 4; 20%), sinusoidal obstruction syndrome/veno-occlusive disease (SOS/VOD) (n = 3; 15%), or subcutaneous autoimmune syndrome (n = 2; 10%). Corticosteroids were administered to 15 patients; of them, 10 (67%) improved clinically after corticosteroids. Based on CTCAEV5.0, the highest severity of ir-GE was grade ≥4 in 11 (55%) patients and four (20%) patients died due to ir-GE. Conclusions: Generalised immune system-related oedema is a new category of adverse event with immune checkpoint inhibitors and is often associated with a life-threatening condition. The pathophysiology may in some cases be related to endothelial dysfunctions, such as SOS/VOD or capillary leak syndrome. Highlights: Generalised oedema occurred in 0.19% of immune-checkpoint inhibitor-treated patients. Generalised oedema was a life-threatening condition with a mortality rate at 20%. Corticosteroids for generalised oedema were effective in 67% of cases. Pathophysiology of generalised oedema related to endothelial dysfunctions.